2019
DOI: 10.1007/s10120-019-00947-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncological feasibility of laparoscopic subtotal gastrectomy compared with laparoscopic proximal or total gastrectomy for cT1N0M0 gastric cancer in the upper gastric body

Abstract: Background The upper gastric body is of particular interest in relation to gastrectomy because this area includes a border; that is, both distal and proximal gastrectomy for early gastric cancer can involve this area. Laparoscopic subtotal gastrectomy (LsTG) is reported to be suitable procedure compared with laparoscopic proximal and total gastrectomy (LPG, LTG), regarding postoperative nutritional status and surgical safety. However, whether LsTG is an oncologically acceptable procedure for early gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…This minimizes subsequent reflux oesophagitis, which may influence food intake, bodyweight, haemoglobin concentration and nutritional status. With previously reported comparable survival, LPG‐DFT may be superior to LSTG.…”
Section: Introductionmentioning
confidence: 58%
“…This minimizes subsequent reflux oesophagitis, which may influence food intake, bodyweight, haemoglobin concentration and nutritional status. With previously reported comparable survival, LPG‐DFT may be superior to LSTG.…”
Section: Introductionmentioning
confidence: 58%
“…Five homogenous ( I 2 = 39%, P = 0.16) studies (690 patients) reported 5-year overall survival rates ( 31 , 34 36 , 41 ). The results revealed that patients who had undergone LTG or LPG had similar 5-year overall survival rates (OR = 1.04, 95% CI: 0.47 to 2.27, P = 0.93, Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the limitations of EG like symptomatic reflux, several additional anti-reflux techniques have been designed, such as the double flap technique (DFT) during EG with valvuloplasty, in which a seromuscular flap is created to avoid reflux 18,19 . In a previous retrospective study performed by Hayami et al, anastomotic complications (4.7% vs. 17.2%) and severe reflux esophagitis with LA grade ≥ B (2.3% vs. 14.9%) occurred less frequently after EG with DFT than after TG, but the difference was not significant (p = 0.093 and p = 0.06, respectively) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous retrospective study performed by Hayami et al, anastomotic complications (4.7% vs. 17.2%) and severe reflux esophagitis with LA grade ≥ B (2.3% vs. 14.9%) occurred less frequently after EG with DFT than after TG, but the difference was not significant (p = 0.093 and p = 0.06, respectively) 19 . Although EG with DFT was excluded from the present meta-analysis because of insufficient data and the heterogeneity of EG combined with DFT due to EG in operative and reflux-related outcomes, the efficacy and safety of this technique should also be evaluated by comparing EG with DFT and other methods in future studies 18,19,65 .…”
Section: Discussionmentioning
confidence: 99%